ANALISIS PEMASARAN SALE PISANG PADA INDUSTRI âDIANAâ DI KOTA PALU - Musdalifah, Musdalifah; Antara, Made; laapo, Alimuddin (AGROTEKBIS, 2018)
The aim of the research was to determine the form of marketing channels, the margin level at each marketing channel and the marketing efficiency of âDianaâ banana saleindustry. The research location was purposively selected with considerations that the industry was one of banana industries that meetthe criteria of efficiency and was run its marketing process accordingly.The numbers of respondents were three people including the industry leader, a worker and a retailer.Â  Data was analyzed using marketing margin and marketing efficiency analyses.Â  The research results showed that the marketing margin was IDR 2,000 at channel one and IDR 5,000 at channel two.Â  The marketing efficiency of the channel two was higher than the channel one as shown by the efficiency value of 15.66 at the first channel and that of 8.00 at the channel two.Â Key Words: Banana sale, âDianaâ industry, and Marketing